2008
DOI: 10.1016/j.cub.2008.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Ypt11 Functions in Bud-Directed Transport of the Golgi by Linking Myo2 to the Coatomer Subunit Ret2

Abstract: A yeast class V myosin Myo2 transports the Golgi into the bud during its inheritance. However, the mechanism that links the Golgi to Myo2 is unknown. Here, we report that Ypt11, a Rab GTPase that reportedly interacts with Myo2, binds to Ret2, a subunit of the coatomer complex. When Ypt11 is overproduced, Ret2 and the Golgi markers, Och1 and Sft2, are accumulated in the growing bud and are lost in the mother cell. In a ret2 mutant that produces the Ret2 protein with reduced affinity to Ypt11, no such accumulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 15 publications
1
39
0
Order By: Relevance
“…It is reasonable to speculate that other Golgi-derived vesicles are transported along astral microtubules by motor dynein. In budding yeast, the actin cytoskeleton plays an essential role in Golgi transport during mitosis (Arai et al, 2008). We failed to observe co-localization of COPI vesicles with actin networks in male meiotic cells (D.K.…”
Section: Dependence Of Copi Vesicle Distribution On Astral Microtubulmentioning
confidence: 83%
“…It is reasonable to speculate that other Golgi-derived vesicles are transported along astral microtubules by motor dynein. In budding yeast, the actin cytoskeleton plays an essential role in Golgi transport during mitosis (Arai et al, 2008). We failed to observe co-localization of COPI vesicles with actin networks in male meiotic cells (D.K.…”
Section: Dependence Of Copi Vesicle Distribution On Astral Microtubulmentioning
confidence: 83%
“…Late-Golgi elements are moved by Myo2p with Ypt11p, a Rab GTPase, and Ret2p, a subunit of the coatomer complex (Rossanese et al, 2001;Arai et al, 2008). Secretory vesicles are moved by Myo2p (Pruyne et al, 1998;Schott et al, 1999) and require the Rab GTPases Ypt31p and Ypt32p (Casavola et al, 2008;Lipatova et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…in figure). Ypt11p has been identified as an adaptor protein that connects late Golgi cisternae to Myo2p through its interaction with the coatomer subunit Ret2p (Arai et al, 2008), as an adaptor for Myo2p on mitochondria (Itoh et al, 2002), as required for the retention of newly inherited mitochondria at the bud tip (Boldogh et al, 2004) and as a docking protein for cER at the bud tip (Buvelot Frei et al, 2006). Ypt11p is a Rab GTPase that is regulated by phosphorylation and degradation (Lewandowska et al, 2013).…”
Section: Box 1 Open Questions In the Field Of Mitochondrial Inheritancementioning
confidence: 99%
“…Of note, although the cER and mitochondria are moved to the bud by two independent motors (Estrada et al, 2003), a defect in ER inheritance has also been shown to impair mitochondrial inheritance. Ypt11p is a Rablike protein that localizes to the cER (Buvelot Frei et al, 2006) and also interacts with Myo2p (Arai et al, 2008;Itoh et al, 2004). Deletion of YPT11 not only prevents the accumulation of cER at the bud tip (Buvelot Frei et al, 2006) but also inhibits the anchoring of mitochondria at the bud tip (Itoh et al, 2002;Swayne et al, 2011).…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation